2015
DOI: 10.1007/s10620-015-3716-7
|View full text |Cite
|
Sign up to set email alerts
|

Patatin-Like Phospholipase Domain-Containing 3 I148M Variant Is Associated with Liver Steatosis and Fat Distribution in Chronic Hepatitis B

Abstract: In our CHB patients, the PNPLA3 polymorphisms influenced the development of liver steatosis, but not fibrosis status. The association of PNPLA3 p.I148M with liver steatosis increased with the greater amount of abdominal fat, irrespective of BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Some studies have demonstrated that the GG genotype effect the risk of HCC development (Falleti et al, 2011;Sato et al, 2014), while most other studies have reported no such association (Nischalke et al, 2011;Guyot et al, 2013;Friedrich et al, 2014). For patients with HBV infection, recent data reported that PNPLA3 polymorphism was independently associated with hepatic steatosis, but not with advanced fibrosis and HCC development (Vigano et al, 2013;Brouwer et al, 2015;Zampino et al, 2015). As a result, these data, as well as our report, suggest an apparent weaker or even no effect of PNPLA3 polymorphism on the risk of HCC in patients with chronic viral hepatitis as compared to those with fatty liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that the GG genotype effect the risk of HCC development (Falleti et al, 2011;Sato et al, 2014), while most other studies have reported no such association (Nischalke et al, 2011;Guyot et al, 2013;Friedrich et al, 2014). For patients with HBV infection, recent data reported that PNPLA3 polymorphism was independently associated with hepatic steatosis, but not with advanced fibrosis and HCC development (Vigano et al, 2013;Brouwer et al, 2015;Zampino et al, 2015). As a result, these data, as well as our report, suggest an apparent weaker or even no effect of PNPLA3 polymorphism on the risk of HCC in patients with chronic viral hepatitis as compared to those with fatty liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic hepatitis B, the association between PNPLA3 and liver damage seems to be limited to liver fat and inflammation but not fibrosis accumulation per se [40][41][42][43][44]. This link does not seem to be modulated by hepatitis B virus genotypes [40,41].…”
Section: Key Pointmentioning
confidence: 94%
“…58 A similar result has been reported in a separate study of 99 individuals with hepatitis B in which the I148M homozygotes had an OR ¼ 13.9 (95% CI 2.2-86.9; p ¼ 0.005) for the presence of severe steatosis compared with individuals lacking this allele. 55 This allele has not been associated with fibrosis or cirrhosis in multiple studies. 55,59,60…”
Section: Effects In Other Liver Diseasesmentioning
confidence: 99%
“…35 The serum ALT level increasing allele at TRIB1 (rs2954021) significantly associates with increased serum levels of total cholesterol, serum LDL-C, serum triglycerides, and serum alkaline phosphatase, but decreased levels of serum HDL-C. 35,53 Variants near TRIB1 have also been associated with adiponectin. 55 The finding that some, but not all genetic variants that predispose to development of NAFLD predispose to related metabolic disease, suggests that genetics may help explain in part the imperfect correlation of these traits with each other. That is, some of the correlation seen between developing metabolic disease may be due to having shared genetic elements that predispose to more than one metabolic abnormality.…”
Section: Pleiotropies Effects On Related Metabolic Traits and Diseasesmentioning
confidence: 99%